Bank Credit Development: A Study of Macro-Prudential Effect - Sebastiana Viphindrartin; Silvi Asna Prestianawati; Ayman Nazzal (Jurnal Ekonomi dan Studi Pembangunan, 2019)
Macroprudential policy is a policy that leads to the analysis of the financials systems as whole as  of financials individuals including banking. This research want to show the effect of macroprudential policy on the development of banking credit in Indonesia by using monthly time series data from January 2010 until June 2017. This research uses several variables namely credits, exchange rates, Return on Assets (ROA), Loan to Deposits Ratio (LDR), Capitals Adequacy Ratio (CAR) and interest rates. The method used in this research is using Autoregressive (VAR). The result of this study indicate that macroprudential policy has an effect on the development of bank credit in Indonesia. Macroprudential policy that is Loan to Deposits Ratio (LDR) have an influence in improving credit development in Indonesia. In addition, the change in interest rate from the BI Rate to BI 7 Day Repo Rate affect the development of credit in Indonesia. Profit earned and capital owned by banks also affects the development of credit in Indonesia. These results are supported by Impulse Response Function (IRF) and Variance Decompotition (VD) tests where macroprudential policy appears stable in response to credit shocks.